G. Simondon’s Theory of Ontogenesis: Between Organism and Technical Object - Žukauskaitė, Audronė (Problemos, 2018)
[only abstract in English; full article and abstract in Lithuanian]The essay analyses Gilbert Simondon’s theory of ontogenesis, which describes being in terms of becoming or genesis. Simondon argues that philosophy should analyse not substantial, complete and self-identical individuals but the processes of individuation. Thus Simondon creates a universal theory of individuation, which is understood as a shift from the pre-individual state to the process of creating an individual, which becomes the starting point for a new process of individuation. For Simondon ontology is based not on identity but on disparity and difference that force individuals to undergo qualitative change. Thus the theory of individuation becomes a universal methodology, which enables comparison between physical, biological, psychosocial and technical individuations. In this sense Simondon’s theory of individuation or ontogenesis can be interpreted as a materialist methodology, which allows for comparison of organic and inorganic, human and non-human individuals.
Keywords: Simondon, individuation, ontogenesis, the pre-individual, the transindividual